Recombinant interferon α (rIFN-α) does not potentiate the effect of iodine excess on the development of thyroid abnormalities in patients with HCV chronic active hepatitis - Minelli, Roberta; Braverman, Lewis E.; Valli, Maria Antonietta; Schianchi, Claudia; Pedrazzoni, Mario; Fiaccadori, Franco; Salvi, Mario; Magotti, Maria Grazia; Roti, Elio (Clinical endocrinology (Oxford), 1999)
OBJECTIVE To determine whether the administration of pharmacological quantities of iodine during interferon‐alpha (rIFN‐α) treatment of chronic viral hepatitis B and C (HCV) would exacerbate the potential adverse effects of rIFNα on thyroid function. DESIGN Thyroid function tests were carried out in 48 euthyroid patients before and during rIFN‐α therapy of HCV. Twenty‐one of these patients were also treated with 10 drops saturated solution of potassium iodine (SSKI, ∼350 mg iodine daily). Eight patients with HCV but not treated with rIFN‐α received 10 drops SSKI. PATIENTS All patients were enthyroid prior to rIFN‐α therapy for HCV or iodine and thyroid function tests were similar in the three groups. MEASUREMENTS Serum free T4, free T3, and TSH concentrations were measured prior to and at 30 and 60 days of rIFN‐α therapy in the three groups of patients. The serum TSH response to TRH was assessed before rIFN‐α therapy and on day 60. Thyroid peroxidase antibodies were measured before and during therapy. RESULTS During the 2‐month study period, similar small but significant decreases in serum FT4 and FT3 and compensatory small significant increases in TSH concentrations were observed in the patients treated with rIFN‐α + iodine and iodine alone but not in the patients receiving rIFN‐α alone. Abnormal thyroid function tests were observed more frequently in patients receiving rIFN‐α + iodine and iodine alone compared to those receiving rIFN‐α alone. CONCLUSIONS Excess iodine administered to patients treated with rIFN‐α induced small changes in thyroid function similar to those observed in patients treated with iodine alone. Thus, rIFN‐α and iodine do not appear to be synergistic in the development of abnormal thyroid function tests over a 2‐month treatment period.